RELIGIOUS VALUES IN JEIHAN SUKMANTORO'S “MATA MBELING JEIHAN” POETRY ANTHOLOGY: NILAI-NILAI RELIGIUS DALAM KUMPULAN PUISI “MATA MBELING JEIHAN” KARYA JEIHAN - Santi Susanti; Tine Silvana Rahmawati (Jurnal Kata : Penelitian tentang Ilmu Bahasa dan Sastra, 2021)
Jeihan Sukmantoro, is a painter and an accomplished poet who pioneered the mBeling Poetry movement along with Remy Sylado, Sanento Yuliman, and other Jeihan colleagues. Among Jeihan's mBeling poems, Jeihan's poetry contains religious values. Jeihan's thoughts of life influence his works from the perspective of the Islamic religion. This study describes and interprets the religious values Jeihan Sukmantoro’s poetry. The method used in this research is interpretive qualitative with literature review techniques related to Jeihan's poetry which has Islamic religious value. The primary data source in this research is Jeihan's poetry in Mata mBeling Jeihan's anthology poetry books. Secondary data sources come from literature and documents that are in line with the main source. The data analysis technique used in this study is a content analysis technique that includes indication, classification, analysis, interpretation, description and confirmation. The validation technique used is the triangulation of data sources, which refers to various sources in the form of literature and documents that support the research data. The results revealed that the religious values expressed in Jeihan's poetry included aqidah, knowledge, ihsan, worship, and piety.